Incidence of diabetic retinopathy and predictors among adult patients with diabetes in central and southern Ethiopia: a multicentre retrospective cohort study - Tagese Yakob; Awoke Abraham; Begidu Yakob; Mesfin Menza Jaldo (BMJ Open)
Objectives This study aimed to determine the incidence of diabetic retinopathy (DR) and predictors among adult patients with diabetes in central and southern Ethiopia.Design A hospital-based retrospective cohort study was conducted.Setting The study was conducted in selected public hospitals in central and southern Ethiopia.Participants A total of 376 adult participants newly diagnosed with diabetes were enrolled from 2015 to 2023, and the follow-up date was from the date of enrolment to the development of events.Outcome measures The data were collected by reviewing their records and entered in EpiData V.4.6.0.2 and exported to STATA V.14 for analysis. Descriptive statistics of the variables were obtained. The Cox proportional hazards assumption was checked. The Cox regression model was used to determine the median time to develop DR and identify predictors of DR. Bivariable and multivariable analyses were done; variables with a value of p<0.05 and a corresponding 95% CI in the final model were used. The model of adequacy was checked.Results Records of a total of 376 adult patients with diabetes were reviewed with a mean baseline age (±SD) of 34.8±10 years. Of the total study participants, half (189, 50.3%) were female. A total of 376 adult patients with diabetes were followed for 45 752 person-months (PMs). Overall, the incidence rate was 11.7 per 1000 PMs of observation. Positive proteinuria (adjusted HR (AHR)=2.19; 95% CI 1.18 to 4.08), hypertension (HTN) (AHR=2.23; 95% CI 1.39 to 3.55) and type 2 diabetes mellitus (AHR=2.89; 95% CI 1.19 to 7.05) were independently significant predictors of DR.Conclusion The overall incidence rate of DR (type 1 and type 2) was high. Adult patients with diabetes with HTN, proteinuria and type of diabetes were independent predictors of DR. The best strategy to protect our eyesight from DR is to control high glucose level and giving due attention to high-risk individuals with diabetes. Thus, health professionals and concerned health authorities should target these factors in their efforts to prevent DR among diabetics.